PENGARUH PERSEPSI KEBERMANFAATAN, KEMUDAHAN PENGGUNAAN, KEPUASAN PENGGUNA, KEAMANAN DAN KERAHASIAAN, DAN KENYAMANAN WAJIB PAJAK TERHADAP PENGGUNAAN E-FILING (Studi Kasus pada Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Klaten) - WULANDARI, YUNI MUHARROMAH; PRATOMO, SIGIT ADHI; IRWANTO, WAHJOE SRI (KIAT BISNIS, 2016)
This research aim to to know the influence of simultan and also parsial from useful perception, use amenity, consumer satisfaction, security and secret, and kenyamaan taxpayer to use e-filing Population in this research is Taxpayer of Person People enlisted by as Taxpayer e-filling inKPP Pratama Klaten. Sampel used at this research as much 100 responder. Data used by primary data by using kuesioner alloted to Taxpayer enlisted in KPP Pratama Klaten with the method of accidental sampling. data Kuesioner in test with the validity test and test the reliabilitas. Test the classic assumption used by test multikolinieritas, test the heteroskedastisitas, and test the normalitas. Method analyse the data used is method analyse the doubled linear regression and analyse the coefficient determinasi (R2). Hypothesis Examination of test F and test the t. Result of this research indicate that the Useful Perception (X1) have an effect on to use e-filing, Use Amenity (X2) have an effect on to use e-filing, Consumer Satisfaction ( X3) have an effect on to use e-filing, security And Secret (X4) have an effect on to use e-filing, Freshment (X5) have an effect on to use e-filing Keyword : Useful Perception, Use Amenity, Consumer Satisfaction, Security And Secret, Freshment, use e-filing